Succeeding as a documentary filmmaker : a guide to the professional world - Rosenthal, Alan, 1936- (Southern Illinois University Press, 2011)
While many film programs prepare students for the realities of Hollywood, comparatively little guidance is provided for the aspiring documentary filmmaker. Alan Rosenthal fills this void with Succeeding as a Documentary Filmmaker: A Guide to the Professional World. Unlike traditional manuals on documentary filmmaking, which focus primarily on the creation of films, this user-friendly volume draws upon real-world examples and the advice of experienced filmmakers to provide essential information about the nonfiction movie business. From the basics of the current film business.